In situ soil respiration in a recently burnt versus unburnt maritime pine plantation - Marques, Ana Filipa Machado (2020)
Wildfires are one of the numerous threats that affect Mediterranean forests, mostly due to climatic factors, abandonment of rural practices and inadequate forest management practices. Climate change has an important role as well due to the increase of temperature and decrease of precipitation. Portugal is one of the most affected countries in Europe by wildfires. The year of 2017 was one of the severest since there are records (the year of 1980) with 442 418 ha of forest burnt. Wildfires have several consequences on soil properties and components, especially on the below-ground biomass and soil organic matter. In order to understand how wildfires, affect carbon dynamics, soil respiration was monitored on a maritime pine plantation during the first six months after the wildfire. The high severity burnt study area was divided in three structural units: under the canopy of the trees without needle cast (UCNN), near a shrub (S), and interpatch without vegetation (IP). To assess the effect of fire the severity on soil respiration, the soil respiration under the tree canopies was monitored also on an area where natural needle cast (UCWN) was present. In addition, the same structural units were monitored in a control site that didn’t burnt in the past 10 years. In a general way, the soil respiration rates were lower in the burnt site compared to the unburnt, and the structural unit that registered the higher soil respiration values was the UC. The presence of needle cast didn’t show major effects on soil respiration Soil temperature and air temperature registered higher values at the UNB site, however for soil moisture the opposite occurred